Menggagas Komunikasi Musikal dalam Pertunjukan Gamelan - Santosa . (Jurnal ILMU KOMUNIKASI, 2008)
Abstract:In this paper I attempt to argue that gamelan performances are not just musical phenomena in which audiences can enjoy the aesthetic of the performances but at the same time they are modes of communication.Using a specific mode audiences can extract messages to conduct musical communication. In eliciting the messages audiences use the â€œconnotative complexâ€ mode where they can get message(s) among other varieties of possible messages.